Penerapan Metode AHP Untuk Menentukan Kualitas Produksi Crude Palm Oil - Siswanto (Universitas Muhammadiyah Sorong, 2024)
Kurnia Luwuk Sejati is a company that operates in the palm oil industry and produces Crude Palm Oil (CPO). In CPO production, the company only determines two indicators used to determine the quality of CPO, namely Free Fatty Acid (FFA), water content (moisture). The National Standardization Agency (BSN) has established CPO standards contained in the Indonesian National Standard (SNI) 01-2901-2006, namely water content (max moisture 0.5%) impurity content (max 0.5%) and Free Fatty Acid (FFA 5 %). This allows companies to add one more indicator to determine the quality of CPO, namely impurity content/impurity content, this is an important factor because producers can know the level of clarity and quality of CPO production and is also a way to increase producers' confidence in buying the company's products. The AHP method is used to select conflicting criteria, which then creates alternatives/solutions that have the highest priority and makes it easier for companies to decide on quality control. The results of this research show that of the three quality control criteria, FFA or free fatty acid content is the company's top priority for improving quality because it has the largest comparative weight of 0.681563, then impurity content with a weight value of 0.236447 and Moisture with a weight value of 0, 08199.